1967
DOI: 10.1177/004051756703701206
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Fabrics in Shear

Abstract: The effect of heat-setting on the properties of a nylon monofil fabric in shear has been investigated, and considerable changes have been found to occur. These changes particularly depend on whether heat-setting is done with the specimen held at fixed dimensions or allowed free contraction. Photographs of the actual contact area at filament crossovers are presented to interpret many of the resulting shear properties. It has also been found that bending properties of the filaments were unaffected by heat-settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a recent paper by Spivak and Treloar [1] it was found that the hysteresis during shearing of a plainweave fabric made from mono-filament nylon yarn increased with the angle of deformation through which the cloth was sheared. It was found that for an angle of approximately 0.075 radians the hysteresis was fully established.…”
Section: July 2 1968mentioning
confidence: 98%
“…In a recent paper by Spivak and Treloar [1] it was found that the hysteresis during shearing of a plainweave fabric made from mono-filament nylon yarn increased with the angle of deformation through which the cloth was sheared. It was found that for an angle of approximately 0.075 radians the hysteresis was fully established.…”
Section: July 2 1968mentioning
confidence: 98%